Hysteresis, Loss and Nonlinearity in Epitaxial PbZr0.55Ti0.45O3 Films: A Polarization Rotation Model. (23rd September 2020) - Lucke, Philip; Bayraktar, Muharrem; Birkhölzer, Yorick A.; Nematollahi, Mohammadreza; Yakshin, Andrey; Rijnders, Guus; Bijkerk, Fred; Houwman, Evert P.
Abstract: The phenomena of hysteresis, ferroelectric loss, and nonlinearity are investigated for the strain and polarization of a monoclinic, epitaxial Pb(Zr, Ti)O3 film over the 70 Hz to 5 kHz frequency range at sub‐coercive excitation fields and zero electrical bias. For the strain, a linear hysteretic behavior is found, whereas the polarization shows a strongly nonlinear hysteretic behavior. In contrast to polycrystalline structures (for instance in ceramics or chemical solution deposited thin films), the commonly referred Rayleigh model cannot explain the observed behavior. A new model is presented, based on the rotation of the polarization vector within the monoclinic or rhombohedral unit cell under an applied electric field, with the viscous interaction of domains accompanying the unit cell deformation. The model explains the amplitude and frequency scaling of the strain, polarization, and loss tangent as well as the observed higher harmonics of polarization in the measured epitaxial Pb(Zr, Ti)O3 films. It is concluded that the nonlinear response and the hysteretic loss originate from two separate physical processes. The nonlinear response is attributed to the nonlinear angular rotation of the polarization vector, whereas the hysteresis and ferroelectric loss are due to a viscous interaction of domains while the polarization vector is rotating. Abstract : Hysteresis, loss and nonlinearity are investigated for the strain and polarization of a monoclinic, epitaxial Pb(Zr, Ti)O3 film. A new model based on the rotation of the polarization vector due to an applied electric field allows full description of the observed experimental behavior. The model shows that the nonlinear response and the hysteretic loss originate from two separate physical processes.